2013
DOI: 10.1186/2047-783x-18-55
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Meta-analysis on the efficacy of tourniquet on ankle trauma surgery

Abstract: BackgroundIn our study, we used meta-analysis to study the efficacy of the tourniquet on ankle trauma surgery. Postoperative infection rate, deep venous thrombosis incidence, hospital stay, and joint range of motion were studied to compare the tourniquet and non-tourniquet groups and provide certain references for clinical decision.MethodsWe searched PubMed, MEDLINE, EMBASE, and the Cochrane controlled trials register for all publications about the efficacy of tourniquet published before November 2012. The qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Certain studies have measured the amount of wound infection after surgery with tourniquet (1,17,23). Wound infection is an important criterion for wound healing, so that increased incidence of infection can be associated with a decrease in wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain studies have measured the amount of wound infection after surgery with tourniquet (1,17,23). Wound infection is an important criterion for wound healing, so that increased incidence of infection can be associated with a decrease in wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Saeid et al (2010) studied the effect of tourniquet in tibia fracture plating surgery, and reported no statistically significant difference in the overall "infection" items between the 2 tourniquet and non-tourniquet groups (1). In their meta-analysis of the efficacy of tourniquet on ankle trauma surgery, Jiang et al (2015) reported no significant difference between the tourniquet and non-tourniquet groups, regarding the amount of postoperative infection (23). In their study on the role of tourniquet in wound infection after fibula fracture surgery, Maffulli et al (1993) found that the use of tourniquet increases the possibility of infection (17).…”
Section: Discussionmentioning
confidence: 99%
“…The Publisher and Editor regretfully retract this article [ 1 ] because the peer-review process was inappropriately influenced and compromised. As a result, the scientific integrity of the article cannot be guaranteed.…”
Section: Retractionmentioning
confidence: 99%